Comparison of Clinical and Radiological Outcomes between Calibratable Patient-Specific Instrumentation and Conventional Operation for Medial Open-Wedge High Tibial Osteotomy: A Randomized Controlled Trial. - Gao, Fawei; Yang, Xucheng; Wang, Chenggong; Su, Shilong; Qi, Jun; Li, Zhigang; Chen, Juehao; Zhong, Da (BioMed Research International, 2022)
Background. High tibial osteotomy (HTO) is an effective surgery in treating medial compartment knee osteoarthritis (KOA) combined with varus deformity. An accurate orthopaedy is the key and challenge to the success of HTO. Therefore, we designed a calibratable patient-specific instrumentation (PSI) to assist surgery and evaluated its accuracy and clinical outcomes by comparing with conventional operation (CO). Materials and Methods. 37 patients (39 knees) with medial compartment KOA were randomly divided into the PSI and CO groups and underwent medial open-wedge high tibial osteotomy (MOWHTO) from September 2020 to May 2021. The postoperative radiological outcomes were compared with the preoperative measurements or target values to evaluate the accuracy of correction in the two groups. The American Knee Society Score (AKSS), complication rate, number of intraoperative radiation exposures, blood loss volume, and operative duration were analysed to evaluate the clinical outcomes in the two groups. Results. The designed target values were better achieved in the PSI group than in the CO group. The mean absolute difference between the postoperative measurements and preoperative targets was significantly lower in the PSI group than in the CO group (weight-bearing line (WBL) ratio, 1.97 ± 1.83 % vs.5.42 ± 4.41 % , P = 0.002 ; hip-knee-ankle (HKA) angle, 1.12 ± 0.86 ° vs. 2.27 ± 1.97 °, P = 0.018). The operative duration was significantly shorter (P = 0.014), and the number of radiation exposures (P < 0.001) and volume of intraoperative blood loss (P = 0.003) were significantly lower in the PSI group than in the CO group. The clinical AKSS score at 3 and 6 months postoperatively and the functional AKSS score at 3 months postoperatively were significantly higher in the PSI group than in the CO group (P = 0.042 , 0.040, and 0.034, respectively). Conclusion. For patients with medial compartment KOA, calibratable PSI can assist the surgeon in MOWHTO with superior accuracy and clinical efficacy. This study was conducted under Randomized Controlled Trial Details (RCT) with Registry Number ChiCTR2000038619.